Sustainability Performance Evaluation of Renewable Energy Sources: The Case of Brazil - Oliveira, João Fernando Gomes de (Springer International Publishing, 2018)
This book presents a unique analysis of the sustainability performance of various renewable energy sources, based on Brazilian case studies. The evaluation also covers the potential held by regions with diverse socioeconomic and environmental characteristics and how they affect the development of each source. Considering that energy is essential to sustaining and improving modern society, the answer to the current energy dilemma lies in the development of a system that comprises multiple renewable, reliable, and sustainable energy sources. Brazil, which has a predominantly renewable electricity grid, has the privilege of being home to a range of different sustainable sources, although most of its electricity comes from hydroelectric power plants. With that in mind, this book has the primary objective of developing a performance evaluation system for important renewable sources in Brazil (solar, wind, and hydro), taking into account different scenarios and investor profiles. The analysis is based on the study of sustainability indicators related to the technical, economic, social and environmental aspects of the evaluated energy systems. As the availability of renewable sources is very location-specific, the scope of this book covers two Brazilian States with distinct characteristics. It makes it possible to determine which renewable energy source is most adequate from a sustainability perspective, and in light of the analyzed scope and investor profile. .